Human immunoglobulin (KIOVIG®/GAMMAGARD LIQUID®) for immunodeficiency and autoimmune diseases: an observational cohort study. (July 2015) - Blažek, Bohumír; Misbah, Siraj A; Soler-Palacin, Pere; McCoy, Barbara; Leibl, Heinz; Engl, Werner; Empson, Victoria; Gelmont, David; Nikolov, Nikolai
Aim: To document the therapeutic efficacy and safety of Human Normal Immunoglobulin 10% Liquid (KIOVIG ® /GAMMAGARD LIQUID ® [IVIG 10%]) under clinical routine conditions.Patients & methods: Subjects received IVIG 10% according to the prescribing information and were followed for 6 ± 1 weeks to 12 ± 2 months depending on indication. Efficacy, adverse events, infusion rates and duration and dose were recorded.Results: Overall efficacy of IVIG 10% was rated as good or very good by the investigator in 81.8% of subjects; overall tolerability was good or very good in 87.5%. One serious adverse drug reaction (ADR) occurred (urticaria); no severe ADRs occurred.Conclusion: In this observational study, the efficacy and safety of IVIG 10% in routine clinical practice was similar to that previously reported in clinical studies.